1994
DOI: 10.1021/bi00193a021
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Linear Dichroism Reveals That A-, B-, and C-DNAs in Films Have Bases Highly Inclined from Perpendicular to the Helix Axis

Abstract: Infrared linear dichroism has been employed to investigate the inclination of the bases in films of poly[d(AC)].poly[d(GT)], poly[d(AG)].poly[d(CT)], and natural DNAs (from Escherichia coli and calf thymus). All DNAs investigated assume the B-form at high (> 94%) relative humidity. Poly[d(AC)].poly[d(GT)], E. coli DNA, and calf thymus DNA assume the A-form at low (75%) relative humidity, whereas poly[d(AG)].poly[d(CT)] assumes the C-form at low (66%) relative humidity. Infrared linear dichroism demonstrates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 71 publications
0
17
0
1
Order By: Relevance
“…The phosphate asymmetric stretching band is now shifted up 2 cm −1 to 1225 cm −1 and is also much broader than observed in solution (50 versus 25 cm −1 ). In the dried state, this band is now clearly composed of two bands near 1234 and 1217 cm −1 with the former suggesting an A‐form conformation42 and the latter, C‐form 50,51. Additionally, the band at 970 cm −1 in the solution spectrum is now shifted to 965 cm −1 , which has been observed for C‐form DNA 50,51.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…The phosphate asymmetric stretching band is now shifted up 2 cm −1 to 1225 cm −1 and is also much broader than observed in solution (50 versus 25 cm −1 ). In the dried state, this band is now clearly composed of two bands near 1234 and 1217 cm −1 with the former suggesting an A‐form conformation42 and the latter, C‐form 50,51. Additionally, the band at 970 cm −1 in the solution spectrum is now shifted to 965 cm −1 , which has been observed for C‐form DNA 50,51.…”
Section: Resultsmentioning
confidence: 70%
“…The infrared spectra of DNA in the region of 1800–800 cm −1 contains a variety of information that is dependent on the composition as well as the conformational arrangement of the DNA double helix. Previous studies have shown that the structure of DNA is highly dependent on its solvation state with a variety of conditions described for the lyotropic transition of the DNA double helix from the normal B‐ to those of A‐, C‐, D‐ or Z‐forms 47–50. The spectra of plasmid DNA in 10 mM Tris pH 7.4 indicates the presence of expected B‐form structure (Fig.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…More recent CD and NMR studies have established that it is A-DNA in aqueous solution (34), and this has been confirmed with chiral probes (35). In addition, linear dichroism studies in neutral aqueous buffer show that the bases of poly(dG)-poly(dC) are more dramatically inclined than observed for B-DNA, and this is characteristic of A-DNA (36). The CD of double-stranded d(CCCCCGCGGGGG) in buffer is similar to that of poly(dG).poly(dC) in buffer (37).…”
Section: Double-stranded D(ggggcccc) Is Composed Of Four D[(ggg)-(cccmentioning
confidence: 86%
“…νC8N9 S10 ) r4,9 νC4N9 S11 ) r2,11 νC2H11 c S12 ) r6,10 νC6 N10 d S13 ) r8,14 νC8H14 S14 ) r9,15 νN9C15 e S15 ) 2 -1/2 ( 1,2,11 -3,2,11) δC2H11 f S16 ) 2 -1/2 ( 1,6,10 -5,6,10) δC6N10 g S17 ) 2 -1/2 ( 7,8,14 -9,8,14) δC8H14 S18 ) 2 -1/2 ( 4,9,15 -8,9,15) δN9C15 h S19 ) γ11,2,3,1 γC2H11 i S20 ) γ10,6,1,5 γC6N10 j S21 ) γ14, 8,7,9 γC8H14 S22 ) γ15, 9,4,8 γN9C15 k S23 ) 6 -1/2 ( 1,2,6 -1,2,3 + 2,3,4 -3,4,5 + 4,5,6 -5,6,1) δ(6-ring 1) S24 ) 12 -1/2 (2 1,2,6 -1,2,3 -2,3,4 + 2 3,4,5 -4,5,6 -5,6,1) δ(6-ring 2) S 25 ) 1/2( 1,2,3 -2,3,4 + 4,5,6 -5,6,1) δ(6-ring 3) S26 ) 6 -1/2 (τ1,2,3,4 -τ2,3,4,5 + τ3,4,5,6 -τ4,5,6,1 + τ5,6,1,2 -τ6, 1,2,3) τ(6-ring 1) S 27 ) 1/2(τ1,2,3,4 -τ3,4,5,6 + τ4,5,6,1 -τ6, 1,2,3) τ(6-ring 2) S28 ) 12 -1/2 (-τ1,2,3,4 + 2τ2,3,4,5 -τ3,4,5,6 -τ4,5,6,1 + 2τ5,6,1,2 -τ6, 1,2,3) τ(6-ring 3) S29 ) (1 + 2a 2 + 2b 2 ) -1/2 [ 4,8,9 + a( 5,4,9 + 7,9,8) 4,5,7 + τ5,7,8,9) + b(τ8, 9,4,5 + τ7,8,9,4)] 7,8,9 -τ9,4,5,7) -(1 -a)(τ7, 8,9,4 -τ8,9,4,5)] τ(5-ring 2) S 33 ) 2 -1/2 (τ6, 5,4,9 -τ3,4,5,7) τ(5/6 ring) 13) νasNH2 S36 ) 6 -1/2 (2 12,10,13 -6,10,12 -6,10,13) l δsNH2 (soring) S37 ) 2 -1/2( 6,10,13 -6,10,12) l δasNH2 (rock) S 38 ) 1/2(τ1,6,10,12 + τ1,6,10,13 + τ5,6,10,12 + τ5,6,10,12) m τNH2 (torsional) S39 ) γ6,10,12,13 n γNH2 (wagging) S 40 ) 3 -1/2 (r15,16 + r15,17 + r15, 18) νsCH3 S41 ) 6 -1/2 (2r15, 16 -r15,17 -r15,18) νasCH3 17) νasCH3 (out-of-plane) S 43 ) 6 -1/2 ( 16,15,17 + 16,15,18 + 17,15,18 -9,15,16 -9,15,17 -9,15,18) o δsCH3 S44 ) 6 -1/2 (2 17,15,18 -16,15,17 -16,15,18) δasCH3 S45 ) 6 -1/2 (2 9,15,16 -9,15,17 -9,15,18) o δasCH3 S46 ) 2 -1/2 ( 16,15,18 -16,15,17) δasCH3 (out-of-plane) S47 ) 2 -1/2 ( 9,15,18 -9,15,17) o δasCH3 (out-of-plane) S 48 ) 3 -1/2 (τ8, …”
Section: Methodsunclassified